IMPLEMENTASI INTEGRASI SAINS AL-QUR’AN DALAM PEMBELAJARAN IPA MATERI SISTEM PERNAPASAN KELAS VIII MTSN 3 BLITAR - Nafi'ah, Farihatun; Filayani, Muhammad Iqbal (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
Creating students who are superior in spiritual and scientific terms can be done through learning activities that integrate Islamic science. The integration of Islamic science in science-biology learning can be done using the Al-Qur'an integration model as a source of inspiration and confirmation. The aim of this research is to describe the planning, implementation and evaluation of the implementation of the integration of science and the Koran in science-biology learning on respiratory system material for class VIII students at MTs Negeri 3 Blitar. The type of research used is descriptive qualitative research with data collection techniques using interview, observation and documentation methods. The results of the research show that of the two class VIII teachers, namely SA1 and SA2, one of them (SA2) implemented the integration of Al-Qur'an science into the respiratory system material which can be seen from the planning, implementation and evaluation stages of the learning carried out. SA1 has not implemented the integration of Al-Qur'an science at the planning and evaluation stages. SA1 has implemented Al-Qur'an science at the implementation stage, but not in the respiratory system material. Therefore, this integration is a form of development carried out by teachers personally so that not all teachers have the ability to implement it.